Clinical Image-Based Procedures. Translational Research in Medical Imaging Third International Workshop, CLIP 2014, Held in Conjunction with MICCAI 2014, Boston, MA, USA, September 14, 2014, Revised Selected Papers - Linguraru, Marius George; Oyarzun Laura, Cristina; Shekhar, Raj; Wesarg, Stefan; González Ballester, Miguel Ángel; Drechsler, Klaus; Sato, Yoshinobu; Erdt, Marius (Image Processing, Computer Vision, Pattern Recognition, and Graphics ;, 2014)
This book constitutes revised selected papers from the Third International Workshop on Clinical Image-Based Procedures, CLIP 2014, held in conjunction with MICCAI 2014 in Boston, MA, USA, in September 2014. The 19 papers presented in this volume were carefully reviewed and selected from 26 submissions.  New strategies are essential to ensure a smooth and effective translation of computational image-based techniques into the clinic. For these reasons CLIP 2014's major focus is on translational research filling the gaps between basic science and clinical applications. A highlight of the workshop is the subject of strategies for personalized medicine to enhance diagnosis, treatment and interventions. Authors are encouraged to submit work centered on specific clinical applications, including techniques and procedures based on comprehensive clinical image data. Submissions related to applications already in use and evaluated by clinical users are particularly encouraged. The event will bring together world-class specialists to present ways to strengthen links between computer scientists and engineers, and clinicians.